HUMAN CAPITAL AS A FACTOR OF INNOVATION DEVELOPMENT IN THE TEXTILE INDUSTRY OF UZBEKISTAN - Popova Nigina Aleksandrovna; Rustamova Maxfuza Maxmudovna (Scholars Digest Publishing, 2024)
This article examines the impact of human capital on the development of innovations in the textile industry of Uzbekistan. It is based on an analysis of current trends and strategies aimed at improving the competitiveness of this sector of the economy. The study examines the role of education, skills of the workforce, and the degree of their compliance with the requirements of the modern labor market in the context of stimulating innovation. Special attention is paid to the assessment of the current state of human capital in the textile industry and the proposed strategies for its development to support innovative processes. The results of the study will reveal the key factors contributing to the effective use of human capital as the main driving mechanism for the development of innovations in the textile industry of Uzbekistan.
Keywords: human capital, innovation development, textile industry, education, workforce qualifications, competitiveness, labor market, development strategies, economic growth.